Effect of the Intensive Plasticizing Zone Design on the Effectiveness of Corotating Twin-Screw Extrusion - Emil Sasimowski; Łukasz Majewski (Advances in Polymer Technology)
The aim of this study was to investigate the effect of a new intensive plasticizing and mixing screw zone design on the effectiveness of the corotating twin-screw extrusion process for talc-filled polypropylene. The study determined the effect of the angle between the trilobe kneading elements forming the intensive plasticizing and mixing zone of the screws, the screw rotational speed, and the polypropylene/talc filling ratio on the characteristics of the extrusion process in a corotating twin-screw extruder EHP-2x20. The paper describes the experimental design and obtained results as well as the developed empirical models for selected variables of the extrusion process.